GRATIS (Gravity-Fed Biofiltering System) : Application of The Water Treatment Technology for Cibaten River in Indonesia - Yudanto, Dea Yusuf; Napitasari, Mita; Suhirman, Suhirman; Syaichurrozi, Iqbal (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2016)
River is one of the resources for water because it is popular for human necessary,especially used in washing, bathing and cooking activity. At this era, the pollution isdesecrated by industrial and domestic waste. Hence, the quality of water on rivers hasdecreased. Cibanten river located in Banten Province-Indonesia country is one of theriver, whose water quality is decreased by pollution. The characteristics of Cibanten riveris Total Dissolved Solid (TDS) of 416 ppm, Total Suspended Solid (TSS) of 100 - 900 ppm,pH level of 6-8. Therefore, watertreatment must be done before the water is used.Biofiltering technology with gravity system was chosen, It utilized the combination ofcoconut fibrous and zeolite active (activation without chemical). This Equipment calledGRATIS (Gravity-fed Biofiltering System). Result from this treatment, TDS decreased to249 ppm (sample 2) and 185 ppm (sample 3), pH increased to 7.23 (sample 3) and 8.5(sample 2), TSS decreased to 9-115 ppm with fed water of TSS about 1048 ppm. Turbiditypoint decreased about 99.5 % (sample 2) and 99.7% (sample 3). BOD (biological OxygenDemand) decreased about 83.9% (sample 2) and 87.1% (sample 3) and COD (ChemicalOxygen Demand) decreased about 30.8% (sample 2) and 38.5% (sample 3).